A Test of Owen Genre Séances: Examining Anomalous Events, Psychosomatic Symptoms, and Electromagnetic Fields - Laythe, Brian Robert (Journal of Scientific Exploration, 2017)
The current study replicated an Owen & Sparrow (1976) genre séance study to examine the relationships between transliminality, psychokinesis (PK), subjective experiences, contagion effects, and variations in electro-magnetic field activity. Eleven participants in two series of mock séance sessions were observed and recorded for anomalous, subjective and somatic experiences. No verifiable PK occurred, but relationships were found between geo-magnetic and electro-magnetic field activity as well as subjective anomalous experiences. Electro-magnetic fields were found to significantly vary across sessions. Transliminality and related measures were not related to subjective reports of external anomalous phenomena. Implications of electro-magnetic and geomagnetic fields associated with subjective anomalous somatic reports and future research are discussed.